Foreign Ownership and Corporate Risk Taking : Evidence from India - Banerjee, Souvik; Mitra, Amarnath; Shukla, Ravindra Nath; Dubey, Ritesh Kumar (Indian Journal of Finance, 2024)
Purpose : The present study examined the effect of foreign institutional (FI) ownership on the corporate risk-taking behavior of Indian firms. Further, it determined the level of FI ownership that moderated the risk-taking behavior in Indian firms. Finally, the paper discussed the implications of this study for corporate investment and corporate risk. Methodology : The paper studied the impact of FI ownership on 174 non-financial firms’ willingness to take on risk between 2001 and 2023 (23 years). Corporate risk-taking behavior was determined in terms of the volatility of earnings from two variables: return on assets and return on equity. Five independent variables, namely FI ownership, firm leverage, firm size, firm age, and return on assets, along with the control variable of sales growth, were used in the study. Panel threshold regression analysis was employed to understand whether FI ownership influenced corporate risk-taking beyond a threshold point. Findings : The results demonstrated that for firms in India, FI ownership had a significant impact on a firm’s risk-taking behavior beyond a threshold point. FI ownership reduced business risk-taking behavior above a certain threshold. However, FI ownership had a negligible influence on a firm’s risk-taking activities below the threshold point. From this study, it can be concluded that the proportion of FI holdings positively influenced a firm’s management discipline. Practical Implications : The findings were significant, especially for emerging economies like India and suggested that market regulators must encourage FI ownership in domestic firms, as the impact of increased participation of FI investors was positive in managing the volatility of a firm’s earnings. The limitation of the present study is that it focused on the relationship between FI ownership and corporate risk-taking behavior of firms, which allows scope for future researchers to investigate relationships between FI ownership and business risks such as operational risk, credit risk, market risk, and liquidity risk among other risks. Originality : The current work concentrated on emerging markets like India and used a large sample of 4,002 firm-year observations to build a threshold model to investigate the impact of FI ownership on the propensity of Indian firms to engage in corporate risk-taking behavior.